If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13j(4j + -32) = 507 Reorder the terms: -13j(-32 + 4j) = 507 (-32 * -13j + 4j * -13j) = 507 (416j + -52j2) = 507 Solving 416j + -52j2 = 507 Solving for variable 'j'. Reorder the terms: -507 + 416j + -52j2 = 507 + -507 Combine like terms: 507 + -507 = 0 -507 + 416j + -52j2 = 0 Factor out the Greatest Common Factor (GCF), '13'. 13(-39 + 32j + -4j2) = 0 Factor a trinomial. 13((-13 + 2j)(3 + -2j)) = 0 Ignore the factor 13.Subproblem 1
Set the factor '(-13 + 2j)' equal to zero and attempt to solve: Simplifying -13 + 2j = 0 Solving -13 + 2j = 0 Move all terms containing j to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 2j = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 2j = 0 + 13 2j = 0 + 13 Combine like terms: 0 + 13 = 13 2j = 13 Divide each side by '2'. j = 6.5 Simplifying j = 6.5Subproblem 2
Set the factor '(3 + -2j)' equal to zero and attempt to solve: Simplifying 3 + -2j = 0 Solving 3 + -2j = 0 Move all terms containing j to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2j = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2j = 0 + -3 -2j = 0 + -3 Combine like terms: 0 + -3 = -3 -2j = -3 Divide each side by '-2'. j = 1.5 Simplifying j = 1.5Solution
j = {6.5, 1.5}
| -n-3n= | | 35k^2-22k-3=0 | | 7k^2-6k+3=0 | | .3x^2=1.2x+.3 | | 11y-31=90 | | 4x^2+600x-4000=0 | | 100x=7234.56(75) | | 3n^2-6n-45=0 | | 2304(3.14)=X | | 12b^2+17b+6=0 | | 2m^2+13m-24=0 | | 13-6f=31 | | 2(x+17)=400 | | n^2+23=0 | | 3c^2-10=13c | | 2x^2-16x+15=0 | | 2x^2+16x+15=0 | | =15y^2+26y+8 | | 53-(5x+11)=5(x+4)+x | | 6x+3y=54 | | p(x)=10x^3-6x^2+4x+8 | | 4w+12-10=16w-10 | | 49+49=225 | | 15(15)=x | | 3(3x-1.9)=7x-5.7 | | 0.4(3x+6)=1.1-(x+2) | | 4y-4+y+42=8y+40-5y | | 37-(2x+9)=2(x+9)+x | | 3z-(2z-5)=5 | | 2*x*x+3x-203238=0 | | 55(45+4)=x | | r^2=-6-5r |